Research on grinding forces of a bionic engineered grinding wheel. (December 2019) - Yu, Haiyue; Zhang, Weilun; Lyu, Yushan; Wang, Jun
Abstract: Higher grinding forces have harmful impact on service life of grinding wheel and surface integrity of workpiece. Large supply of cutting fluid is often used to lower grinding force by improving lubrication condition, but it will cause various environmental threats. In this paper, an engineered grinding wheel (EGW) bio-inspired by phyllotaxis was developed to lower grinding forces with eco-friendly process, and the characteristic of the bionic EGW about grinding forces was studied. After conducting the contrast experiments of grinding forces generated by some EGWs and Non-EGW for the workpiece of titanium alloy, the results were obtained: the bionic EGW could obtain lower grinding forces because of its higher utilization of grinding fluid and bigger density of dynamic cutting points (DCP); The grinding forces of bionic EGW was negative correlation with phyllotactic coefficient. This research will supply new theoretic foundation for the development of high-efficiency and green grinding.